State-building after disaster: Jiang Tingfu and the reconstruction of post-World War II China, 1943-1949 - Mitter, R (Cambridge University Press, 2018)
Post-World War II reconstruction in Europe and Asia is a topic of growing interest, but relatively little attention has been paid to the relief and rehabilitation effort in China in the immediate post-1945 period. This article reassesses the postwar program implemented by the Chinese Nationalist (Guomindang) government and the UNRRA (the United Nations Relief and Rehabilitation Administration), not just in terms of humanitarian relief, but also as part of a process that led to new thinking about the nature of the postwar state in Asia. It focuses on the ideas and actions of Jiang Tingfu (T. F. Tsiang), head of the Chinese National Relief and Rehabilitation Administration that worked with UNRRA. Chinese ideas for reconstruction in China were simultaneously statist, international, and transnational, and were shaped by high modern ideas drawn from Soviet and American examples. They were also influenced by China's poverty and wartime vulnerability, which made locally directed solutions more relevant in areas such as public hygiene. Success was unlikely because of the incipient Chinese Civil War and the huge demands of reconstruction on a state that was near-destitute, with a destroyed infrastructure. Nonetheless, its characteristics still bear examination as a first, tentative chapter in a longer story of post-imperialist and Cold War state-building that would shape countries in Asia and beyond.